2021
DOI: 10.1186/s12879-021-06142-3
|View full text |Cite
|
Sign up to set email alerts
|

A case report of endocarditis and spondylitis caused by Brucella melitensis biovar 3

Abstract: Background This case report describes the clinical process of a shepherd who suffered brucellosis-related endocarditis (BE) and spondylitis (BS) and was infected with Brucella melitensis biovar 3 (B. melitensis biovar 3). Case presentation A 55-year-old male patient was admitted to The First Affiliated Hospital of Shihezi University on October 11, 2018, due to over 3 months of intermittent fever, back pain, and heart trouble. The Rose Bengal Plate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…It is worth noting that a spinal epidural abscess is an infrequent complication that may occur during spondylitis caused by Brucella species [ 7 ]. Spine brucellosis is a relatively rare but potentially debilitating form of the disease [ 8 ]. Epidural abscesses most commonly affect the lumbar vertebrae, while their involvement in the cervical spine is relatively rare.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that a spinal epidural abscess is an infrequent complication that may occur during spondylitis caused by Brucella species [ 7 ]. Spine brucellosis is a relatively rare but potentially debilitating form of the disease [ 8 ]. Epidural abscesses most commonly affect the lumbar vertebrae, while their involvement in the cervical spine is relatively rare.…”
Section: Introductionmentioning
confidence: 99%
“…Infected aneurysms and aortic ulcers are uncommon, but they can be fatal as well 6 . According to some research, Brucella‐related endocarditis accounts for fewer than 1% of all brucellosis cases 7 . In Brucella endocarditis, the aortic valve is most frequently impacted, whereas the mitral valve is infrequently affected 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have reported that Brucella melitensis (B. melitensis) biovar 3 is the predominant wild strain in Xinjiang. This strain has been isolated from milk, aborted sheep fetuses, human blood, and Asian badgers (5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%